Experimental study of thermal fragmentation of lignite in drying process. Issue 13 (3rd October 2019) - Miao, Zhenyong; Chen, Jingpeng; He, Qiongqiong; Wan, Yongjiang; Wan, Keji; Gao, Mingqiang
Abstract: This paper investigated the thermal fragmentation of three lignite samples with temperature of 100 °C–200 °C and drying time of 0–90 min using the fixed bed reactor. The effects of a variety of factors such as temperature and drying time on fragmentation ratio were studied. The results showed that fragmentation ratio was positively related to temperature and drying time, and the degree of fragmentation was different for different lignite samples. Additionally, it was demonstrated that the point load strength remarkably decreased with the increase of temperature and drying time. The fragmentation ratio as a function of point load strength represented that lignite with higher strength had a lower fragmentation ratio, and the possibility of secondary fragmentation of dried lignite decreased with the increase of point load strength. Fragmentation ratio decreased with the increase of lignite density. The mineral matters of lignite significantly had influence on fragmentation. The mass inhomogeneity degree was given to depict the mineral element compositions. A fragmentation prediction equation was established based on mass inhomogeneity degree, which was associated with moisture content and ash content.